THE EFFECTIVENESS OF GAMIFICATION TECHNOLOGIES IN ENGLISH LANGUAGE TEACHING - Nazarova Sevinchoy Umarbekovna (TADQIQOTLAR, 2026)
Abstract This article discusses the effectiveness of gamification technologies in English language teaching. Increasing learners’ motivation, engagement, and academic performance is one of the major goals of modern education. This study investigates the use of gamification elements (points, badges, leaderboards, levels and rewards) to improve language learning outcomes. The results suggest that gamification is beneficial for students’ motivation, participation and language skills. Additionally, gamified learning settings help develop the abilities of independent learning and enhance the educational experience through a more interactive approach.